(untitled) (Jurnal Adabiya, 2020)
Media oftransferis one oftherightsteps undertaken bythelibrary inmaintainingthe quality ofthe collectioninformationit has. With pairs overthismediawill certainlybe apositivemeaningforthelibrary.As doneinlibraryofDianNuswantoroUniversity Semarang, by using media transfer activities for the collection that can be exhaled, accessibility information retrieval, mengheat storage space collection both on display shelves and warehouses. This may be done by using the media as a form of activity in maintaining and using documentsto improve over a long period of time andmay be used by future generationswithout prejudice to the information contained in documentsthatmay inthe longrunbe physically damaged.